Analisis Kinerja Pembangunan Kabupaten Jeneponto Dengan Metode Logical Framework Analysis - Tobara, Sevenia; Alam, Syamsu; ., Regina; ., Irwandi; Kamaruddin, Citra Ayni (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to analyze the factors behind the low development performance in Jeneponto Regency. The analysis method used is the Logical Framework Analysis method. The results showed that the factors behind the low development performance in Jeneponto Regency, especially in the fields of education and health, are the low quality of education and the low level of public health. The low quality of education is characterized by the low average length of schooling of the community there which is caused by high dropout rates where the average cause of dropout rates is economic inability, socio-cultural factors some children choose to marry or be married off at school age, and the absence of motivation to go to school so that children choose to work. Meanwhile, the low level of public health is caused by the low life expectancy of the people of Jeneponto. The low life expectancy of the community is caused by the low achievement of optimal service standards (SPM) where the cause of the low achievement is due to inadequate facilities and infrastructure and health services that are not yet optimal.